1990
DOI: 10.1177/019791839002400101
|View full text |Cite
|
Sign up to set email alerts
|

Racial and Ethnic Inequality in the United States, 1940 and 1950: The Impact of Geographic Location and Human Capital

Abstract: "This article examines the trend in ethnic stratification from 1940 to 1950, a decade that has been viewed as a critical turning point in race and ethnic relations in the United States.... It begins with a brief overview of ethnic diversity in the United States and a descriptive account of ethnic differentiation and inequality. Then it tests--in a preliminary fashion--several hypotheses about the role of socioeconomic and geographical forces in shaping ethnic occupational inequality across this significant in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
15
0

Year Published

1994
1994
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 33 publications
0
15
0
Order By: Relevance
“…On the other hand, for specific ethnic populations -Central and Eastern Europeans, and Scandinavianslocation in specific labor markets represents an important opportunity for economic status. Thus, for certain groups, our research has shown that location does matter, but generally matters less than other background factors (Hirschman and Kraly, 1990).…”
Section: Perspectives On the Role Of Geographic Location In Racial Anmentioning
confidence: 62%
“…On the other hand, for specific ethnic populations -Central and Eastern Europeans, and Scandinavianslocation in specific labor markets represents an important opportunity for economic status. Thus, for certain groups, our research has shown that location does matter, but generally matters less than other background factors (Hirschman and Kraly, 1990).…”
Section: Perspectives On the Role Of Geographic Location In Racial Anmentioning
confidence: 62%
“…For biracial Americans the risks incurred by embracing a stigmatized identity involve their emotional well-being. If they invest themselves totally in the effort and the effort doesn't pay off and if they see that equality in the job market has eluded them in the process, they will face a profound devastation and lose all respect for societal institutions (Hirschman and Kraly, 1990). The alternative to taking risks -particularly if one is lightskinned -is to distance oneself from the stigmatized community.…”
Section: Biracial Experiencementioning
confidence: 99%
“…Assumptions by law enforcement officers of culpability have sparked controversy and protest. In fact, assault of African-American males by law enforcement officers frequently has little to do with race and is arguably attributable to having dark skin particularly where males are concerned (Hirschman and Kraly 1990). Skin color is the universal clue to race as those who commit racist acts do so on the basis of what they conclude about racial identification visually.…”
mentioning
confidence: 99%